DIAGNOSIS DAN INSIDENSI PENYAKIT ANTRAKNOSA PADA BEBERAPA VARIETAS TANAMAN CABE DI KOTA BITUNG DAN KABUPATEN MINAHASA - Ratulangi, Max M.; Sembel, Dantje Terno; Rante, Caroulus S.; Dien, Moulwy F.; Meray, E. R; Hammig, M.; Shepard, M.; Carner, G.; Benson, E. (EUGENIA, 2012)
ABSTRACT This study was carried out in the laboratory and in the field at City of Bitung, Districts of Minahasa. The cause of disease was studied in the laboratory and the percentage of insidence of disease was carried out in the field. Results showed that the cause of antracnose disease in North Sulawesi was Colletotrichum gloeosporioides (Penz.) Penz & Sacc. in Penz (Cg). Computation of the antracnose disease insidence showed that variety white hot chili has the highest disease insidence which is 16.50% followed by green hot chili 10.13%, and the lowest is curled chili which is 9.03%. The different in this rate is affected by pathogen, host plant and the environment. Field observation showed that this disease has already spread at all chili plantation at the City of Bitung and District of Minahasa. Keywords: Chili, antracnose, Colletotrichum gloeosporioides